Technology for prosodic variation - Aurrekoetxea, Gotzon; Iglesias, Aitor (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2010)
This contribution is included in the "Corpora of Spoken Dialects of the Basque Language-EDAK" project, which aims to create the prosodic multimedia atlas of the Basque language. It presents the first outcome taking into account data from two localities situated in the Western part of the Basque territory: Ondarroa and Larrabetzu. Although both belong to the Biscayan dialect, they have a different accentual system. Apart from the computer tools being used in the project, this paper deals with the sociolinguistic differences that exist in both localities between two generations (adults and young people) and the geolinguistic differences between these two localities.